The effect of combining primers and cements from different cement systems on the bond strength between zirconia and dentin - Minh Le; Evaggelia Papia; Christel Larsson (Nature Publishing Group, 2024)
Abstract Objective The aim of this study was to evaluate the influence of combining primers and cements from two different resin cement systems on the microtensile bond strength (μTBS) between zirconia and human dentin. Materials and methods A total of 120 specimens of zirconia cemented to dentin were allocated into eight groups based on cement type (RelyX Ultimate or Panavia V5) and primers (Tooth Primer, Clearfil Ceramic Primer and Scotchbond Universal Adhesive) combinations, applied to dentin or ceramic surfaces. Following artificial aging with 5000 thermocycles, μTBS tests were conducted. Statistical analysis was performed using One-way ANOVA and Tukey's post hoc tests (p ≤ 0.05), and failure modes were assessed. Results The Panavia V5 cement system demonstrated the highest bond strength (19.4 ± 4.4 MPa), significantly higher than the other groups except when RelyX cement was used with Panavia primers (16.9 ± 3.7 MPa). Cohesive fractures within the cement layer were the predominant failure mode. Conclusions The combination of primers from different adhesive cement system brands may significantly affect the bonding effectiveness. Therefore, using products from a single product line of the same adhesive cement system, and following the manufacturer's recommendations for indications and use, is crucial for a more predictable clinical outcome.